Optimizing Critical Thinking Skills Through Wizer.Me-Based E-Module Development Using Discovery Learning Model in Basic Physics - Susanti, Ernita; Makiyah, Yanti Sofi; Sulistyaningsih, Dwi; Rizal, Rahmat (STKIP Singkawang, 2025)
In recent years, fostering critical thinking skills in students has become a priority in higher education, particularly in physics courses where analytical thinking is essential. This research aimed to develop an e-module based on the discovery learning model using Wizer.me to optimize students' critical thinking skills in basic physics courses with valid and practical criteria. This research uses research and development (R&D) methods with McKenney's development model. The data in this research are needs analysis data, validation data, and practicality data. The research instrument consisted of analysis sheets, validity, and practicality questionnaires. The data analysis technique uses descriptive percentages. Based on the research results, the e-module based on the discovery learning model using Wizer.me has been proven valid and practical in optimizing students' critical thinking skills in basic physics courses. This e-module can be implemented as an effective learning tool to enhance students' critical thinking abilities.